Paired box 7 (Pax7) gene: molecular characterisation, polymorphism and its association with growth performance in goose (Anser cygnoides). Issue 6 (2nd November 2017) - Wang, C.; Yang, Y.Z.; Liu, Y.; Gong, S.M.; Wang, H.Y.; He, D.Q.
ABSTRACT: 1. Paired box (Pax7) gene is a member of the paired box family and plays a critical role in animal growth and muscle development. However, the molecular characterisation of the goose Pax7 gene is unknown. 2. The open-reading frame of goose Pax7 is composed of 1509 bp, which encodes a protein of 503 amino acids and shares high homology with Pax7 of other birds. 3. Ten single-nucleotide polymorphisms were identified in the genomic DNA sequence, 8 located in the intron region and two located in the exon region. 4. Association analysis showed the C122T locus was significantly associated with the body weight of Zhedong-White geese in week 4, 6, 8, 10 and 12. 5. It was concluded that the goose Pax7 gene may be an important candidate gene for goose growth traits and marker-assisted selection.